Compère Général Soleil de Jacques Stephen Alexis, entre chant de liberté et critique écopoétique - Faouzia Righi (Études Caribéennes)
In Compère Général Soleil, the narrator describes Haitian socio-politic reality with a poetic language. He makes a link between political failure of corrupt elites and ecological degradation. Jacques Stephane Alexis is among the first writers in French speaking and Caribbean area who establishes such a link. Ecopoetic interpretation offers us a fresh look towards his first fiction. Thanks to a close cultural relationship between Haitians and nature, a democratic future is imagined. The Anthropocene is also indirectly announced through the criticism of American occupation.